Measuring the level of quality of hotel services provided in hotels operating in the city of Al-Khoms (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study aimed to know the level of quality of hotel services provided in hotels operating in the city of Khoms from the point of view of their guests during the month of July 2022. The descriptive approach was adopted to reach accurate and detailed knowledge about the problem of the study. The study included all (488) hotel guests operating in the city of Al-Khoms during the month of July 2022, and a sample size of (200) individuals was taken. The number of questionnaires that were analyzed was 159, or 73.3%. The statistical processing of the data was done using a program SPSS statistical packages, It concluded that the level of quality of hotel services provided in hotels operating in the city of Al Khoms was very high from the point of view of its guests during the month of July 2022, and recommended increasing interest in developing and improving hotel services in line with the needs of its beneficiaries, through coordination with the Ministry of Tourism to help provide needs. necessary, and employing them to serve the beneficiaries of hotel services in the hotels under study.
Keywords: hotel; hotel guests; hotel services; quality of hotel services; the city of Khoms